Does antenatal micronutrient supplementation improve children's cognitive function? Evidence from the follow-up of a double-blind randomised controlled trial in Nepal. Issue 1 (28th February 2018) - Dulal, Sophiya; Liégeois, Frédérique; Osrin, David; Kuczynski, Adam; Manandhar, Dharma S; Shrestha, Bhim P; Sen, Aman; Saville, Naomi; Devakumar, Delan; Prost, Audrey
Abstract : Introduction: Multiple Micronutrient (MMN) supplementation during pregnancy can decrease the proportion of infants born low birth weight and small for gestational age. Supplementation could also enhance children's cognitive function by improving access to key nutrients during fetal brain development and increasing birth weight, especially in areas where undernutrition is common. We tested the hypothesis that children whose mothers received MMN supplementation during pregnancy would have higher intelligence in early adolescence compared with those receiving Iron and Folic Acid (IFA) only. Methods: We followed up children in Nepal, whose mothers took part in a double-blind Randomised Controlled Trial (RCT) that compared the effects on birth weight and gestational duration of antenatal MMN versus IFA supplementation. We assessed children's Full Scale Intelligence Quotient (FSIQ) using the Universal Non-verbal Intelligence Test (UNIT), and their executive function using the counting Stroop test. The parent trial was registered as ISRCTN88625934 . Results: We identified 813 (76%) of the 1069 children whose mothers took part in the parent trial. We found no differences in FSIQ at 12 years between MMN and IFA groups (absolute difference in means (diff): 1.25, 95% CI −0.57 to 3.06). Similarly, there were no differences in mean UNIT memory (diff: 1.41, 95% CI −0.48 to 3.30), reasoning (diff: 1.17, 95% CI −0.72 to 3.06), symbolic (diff: 0.97, 95% CI −0.67 to 2.60) or non-symbolic quotients (diff: 1.39, 95% CI −0.60 to 3.38). Conclusion: Our follow-up of a double-blind RCT in Nepal found no evidence of benefit from antenatal MMN compared with IFA for children's overall intelligence and executive function at 12 years.